(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The doctrine of socialism as a just social order has a long history and has always provoked debate. The emergence of “real socialism” has not eliminated the disagreements regarding it. Based on an examination of various perspectives on socialism, the author concludes that the very approach to defining socialism is incorrect. Socialism should be viewed as a necessary stage in the development of society, namely, as a necessary transitional state between its class and classless periods. In a class society, participants in production are divided into managers, who privately own the means of production, and workers, who own only their own labor force. Consequently, the former dominates the latter. A classless society presupposes the abolition of private property and its replacement by public ownership. But here a contradiction arises. The transition between a class and a classless society, due to their contrasting natures, is a complex and lengthy process. And since property is a relationship between people over the means of production, realized in their shared production process, society cannot simultaneously possess both forms of ownership due to their diametrically opposed nature. Therefore, an intermediate transitional stage is objectively necessary, in which neither private nor public ownership of the means of production exists. This seems illogical and impossible. However, if we consider that property is not a holistic phenomenon but consists of three components: ownership, disposal, and use, then the division of these three powers of ownership among different social groups allows for a natural transition between a class and a classless society. This article examines how this process was successfully implemented in countries striving to build socialism, primarily in the USSR and now in the PRC, and offers predictions about the future course of this process worldwide.